Population pharmacokinetics and dosing optimization of teicoplanin in children with malignant haematological disease. (5th September 2015) - Zhao, Wei; Zhang, Daolun; Storme, Thomas; Baruchel, André; Declèves, Xavier; Jacqz‐Aigrain, Evelyne
Abstract : Aim: Children with haematological malignancy represent an identified subgroup of the paediatric population with specific pharmacokinetic parameters. In these patients, inadequate empirical antibacterial therapy may result in infection‐related morbidity and increased mortality, making optimization of the dosing regimen essential. As paediatric data are limited, our aim was to evaluate the population pharmacokinetics of teicoplanin in order to define the appropriate dosing regimen in this high risk population. Methods: The current dose of teicoplanin was evaluated in children with haematological malignancy. Population pharmacokinetics of teicoplanin were analyzed usingnonmem software. The dosing regimen was optimized based on the final model. Results: Eighty‐five children (age range 0.5 to 16.9 years) were included. Therapeutic drug monitoring and opportunistic samples ( n = 143) were available for analysis. With the current recommended dose of 10 mg kg –1 day –1, 41 children (48%) had sub‐therapeutic steady‐state trough concentrations ( C ss, min <10 mg l –1 ). A two compartment pharmacokinetic model with first order elimination was developed. Systematic covariate analysis identified that bodyweight (size) and creatinine clearance significantly influenced teicoplanin clearance. The model was validated internally. Its predictive performance was further confirmed in an external validation. In order to reach the target AUC of 750 mg l –1  h 18 mg kg –1 was required for infants, 14 mg kg –1 for children and 12 mg kg –1 for adolescents. A patient‐tailored dose regimen was further developed and reduced variability in AUC and C ss, min values compared with the mg kg –1 basis dose, making the modelling approach an important tool for dosing individualization. Conclusions: This first population pharmacokinetic study of teicoplanin in children with haematological malignancy provided evidence‐based support to individualize teicoplanin therapy in this vulnerable population.